Differential vascular adaptive response to stress exposure in male and female rats: Role of gonadal hormones and endothelial cells - Lanza, Ubirajara; Cordellini, Sandra (Taylor & Francis Ltd, 2007)
Although there are reports concerning a vascular adaptive response to stress in males, this is not yet defined in females. The aim of this study was to delineate functional gender differences in the rat vascular adaptive response to stress and to determine the ability of sex hormones to modulate the stress-induced vascular adaptive response. Responses to noradrenaline were evaluated in aortas, with and without endothelium, from intact, gonadectomized and gonadectomized-hormone-replaced males and females submitted or not to stress (2-h immobilization). Reactivity of the aorta of stressed and non-stressed intact males and females (n = 6-14 per group) was also examined in the presence of L-NAME or indomethacin. Stress decreased and gonadectomy increased maximal responses to noradrenaline in aortas with intact endothelium from both genders. Stress also reduced noradrenaline potency in males. In females, but not males, stress decreased the gonadectomy-induced noradrenaline hyper-reactivity to near that of intact non-stressed rats. Hormone replacement restored the gonadectomy-induced impaired vascular adaptive response to stress. L-NAME, but not indomethacin, abolished the stress-induced decrease in aorta reactivity of males and females. None of the procedures altered reactivity of aortas denuded of endothelium. Conclusion: Stress-induced vascular adaptive responses show gender differences. The magnitude of the adaptive response is dependent on testicular hormones and involves endothelial nitric oxide-system hyperactivity.
Keywords: gender; endothelium; immboilization; vascular reactivity; nitric oxide synthase; prostaglandin